Early experience with cap-assisted endoscopic pancreatic necrosectomy: A technique to enhance safe tissue extraction and decrease interventions - Puri, Nishant; Hallac, Alexander; Srikureja, Wichit (Endoscopy International Open, 2019)
Background and study aim Endoscopic treatment of walled-off pancreatic necrosis (WOPN) has been established as an alternative to operative intervention for well selected patients for many years. Patients and methods A retrospective database of patients who underwent cap-assisted endoscopic necrosectomy of symptomatic or infected WOPN using the assistance of a sterilized banding cap was constructed. All procedures were performed at a single center between January 2017 and June 2018. Results Eight patients met the inclusion criteria for this study. Contrast computed tomography scan was obtained between the initial percutaneous or trans-gastric access and initial necrosectomy. The WOPN had a median length of 9.5 cm (range 3.2 – 14) and width of 5.3 cm (range 2.8 – 11.6). Median duration of endoscopic debridement was 69 minutes (range 21 – 105). Four of six patients underwent a second debridement with a median duration of 95 minutes (range 16 – 108). No periprocedural adverse events occurred. Follow-up was at 6 months, and there were no additional endoscopic or percutaneous interventions for recurrent pancreatic fluid collections. Conclusion The technique of cap-assisted necrosectomy can allow for safe and efficient method of endoscopically treating WOPN.